Research on Basic Issues of State-Owned Asset Management in Higher Education Institutions - Wang, Jianqiang (Asia Pacific Economic and Management Review, 2025)
In recent years, the quantity, quality category and form of state-owned asset allocation of colleges and universities have undergone a fundamental transition and transformation from extensive to precise, management to performance, single allocation mode to efficient utilization, and from property ownership to shared utilization, which also fundamentally reflects the overall requirements and reform achievements of comprehensively deepening reform in the field of state-owned asset management since the 18th National Congress of the CPC. Based on the reform of delegating powers, enhancing regulation and strengthening public service, this paper analyzes the inherent bottlenecks and contradictions in the operation, supervision and performance evaluation of state-owned asset management, as well as the shortcomings and deficiencies in the construction of governance system and governance capacity. From the perspective of control specification, the path and measures to standardize the management of state-owned assets are proposed, and the improvement of quality and efficiency, resource allocation, performance management and whole-process supervision are taken as the core values and ultimate goals of improving the governance system and governance capabilities. The ultimate value of state-owned assets management is realized from two dimensions: the reform of delegating powers, enhancing regulation and strengthening public service, and living on a tight budget.